The reality of rural women in their knowledge of the condition suitable for the Saved of some types of food and the reduction of pollution (Journal of the College of Basic Education, 2023)
The aimed of the research was to highlight The reality of rural women in their knowledge of the condition suitable for the Saved of some types of food and the reduction of pollution . It includes the following fields: the first one is determination of the types of household food which is subjected to decomposition & the level of its decomposition (which includes: regular temperature “room temperature preservation”, low temperature “cooling” preservation & very low temperature “freezing” preservation). As for the second field; determination of the level of knowledge of the countrywoman to the methods used to preserve some kinds of food. It includes the following: style of food preservation in room temperature which in turns includes: vegetables & fruits preservation. Also it includes style of food preservation in low temperature (cooling) for some kinds of food, milk & its derivatives. Style of food preservation in very low temperature (freezing) which includes: preservation of some kinds of food & meat.The study population included (1080) countrywomen in Rashdiya district. A random sample of an average 10% has been taken from the total number; 108 females were included in the study sample. The status of knowledge of the countrywoman in food preserving for some kinds of food & restrict its contamination is used as a scale. The scale passed through six stages to be developed & 88 items were distributed on (2) fields & (7) sections; (20) items were about exposure of some kinds of food for deterioration & (68) items were about knowledge of countrywoman about the ways of preserving the integrity of some kinds of food. Data were collected in May & June, 2010 by survey & direct interview. The data were treated quantitatively & analyzed statistically by using Pearson correlation formula, Spearman correlation formula, SD, mean & percentage. The results showed that the highly decomposed materials were the pickles & chickens while the least decomposed was the white flour, milk & fish. It also turned that the knowledge of the interviewed women in the style of preserving the food was intermediate.According to the results, the research recommends to improve the structure of the countrywoman knowledge concerning preservation of integrity of (pickles, fruits & chickens) through the all types of media & activate the role of the extensive organizations on local & provincial levels to produce & execute extensive programs concerning the integrity of food for the countrywomen in the province.